Machine learning: A simplified approach - Bhat, Subramanya (New Delhi: Narosa Publishing House, 2025)
This text book is designed as a self contained, comprehensive study material for students, faculty and practicing professionals. It serves as a study material for all branches of engineering, technology and sciences. Concepts are explained in a simplified manner, followed by mathematical analysis and implementation of different Machine Learning algorithms.
Includes appendix and references
Keywords: Machine learning -- Artificial intelligence -- Algorithms